THE EFFECT OF ABSORBERS FORMATION ON THE SOUND DIFFUSE REFLECTION - Khaliddazia, Yenni
The growth of biophilic architectural that emphasizes the comfort, health and productivity of humans requires comfort of visual, air, lighting, and acoustic. This principle affects various building typologies including office design. In achieving a good acoustic condition in the work area, sound absorbers are the main part in efforts to control reverberation time. Due to aesthetic and acoustic needs, the design of sound absorbers varies. These variations in the geometry of absorbers design have an impact on the absorption performance and sound reflections as a result of the slopes and air cavities that are formed. In this study, the absorption and diffusivity of absorbers in a zigzag shape and a combination of materials were observed, and their effects on the context. The case study in this research is an open plan office which is a popular office layout nowadays and has requirements of acoustics treatments. The material chosen is Polyethylene Terephthalate (PET) and as a combination Binary Amplitude Diffsorber (BAD) panels are also used to provide a wider range of absorption coefficient. There are 4 scenarios tested: PET with flat and zigzag, and a combination PET and BAD panels with flat and zigzag shapes. The size of the prototype is 1.2 x 2.4 meters, which consists of 8 modules measuring 0.6 x 0.6 meters. The absorption coefficient of the prototype was tested to validate the reference and to know the absorption coefficient when the material was zigzagged and combined. Furthermore, the prototype was tested for diffusivity using CATDDC software in the anechoic room. Diffusivity testing was carried out using 37 microphones and 5 speakers. From this test, the diffusion coefficients of the 4 prototype scenarios are obtained. After that, a room acoustic simulation is performed to determine the impact of diffusivity on open plan office model. The diffusion coefficient from the test is used as a reference for room acoustic simulation with software CATT-Acoustic v9. The results of the diffusion test show that the more diffusive reflection is shown by the zigzag-shaped prototype as a result of the tilted arrangement of the panels which prevents the sound from reflecting as specular reflection. The configuration with the combined material also increases diffusivity as a result of the impedance difference at the surface, so that the resulting a more diffusive reflection. The room acoustic simulation results show that there are differences in the acoustic conditions produced by the scattering coefficient. The difference can be observed in the SPL distribution, the zigzag ceiling shape shows a decrease in the level of the sound distribution at a certain distance compared to the flat shape. The decrease in SPL is different for each frequency with a difference between 1-3 dB. However, for other parameters the changes were not significant: changes in the reverberation time parameter (T30) <0.2 seconds, the distraction distance (rD) <0.5 m, and the privacy distance (rP) <1 m.